Budaya di Madrasah Tsanawiyah Al-Ishlah Tulung Selapan Kabupaten Ogan Komering Ilir - Randi Febriyansah; Mulyadi Eko Purnomo; Akmal Hawi (Bahasa Indonesia, Bahasa English, 2019)
This research is titled "Culture in Tsanawiyah Al-Ishlah Madrasah Tulung Selapan Ogan Komering Ilir Regency". Researchers want to analyze how culture and the factors that influence the formation of culture in Madrasah. This research is a qualitative ethnographic method. Researchers conducted observations, interviews, and document studies, then carried out domain analysis, taxonomic analysis, compound analysis, and analysis of cultural themes. The results of cultural research in Madrasah, namely; First, madrasah have a work philosophy, religious values, care for the environment and discipline, madrasah beliefs that a good education will produce quality graduates. Secondly, the integrated madrasah design is functionally integrated. Third, the organization's systems, mechanisms, and procedures are set out in the madrasah regulations. Fourth, the vision and mission of the madrasah aims to produce quality graduates. Fifth, Madrasah motto 'Al-Ishlah Is Better, Better to Al-Ishlah'. Sixth, Behavior among madrasas, that is, please help, respect and maintain environmental cleanliness. Seventh, madrasah used to carry out religious rituals, orderly, time discipline, independent, and diligent. Eighth, the factors that influence the formation of culture are internal and external factors in madrasah. Madrasah culture is religious culture, caring culture, discipline culture, orderly culture, and independent culture.